Gene methylation in rectal cancer: Predictive marker of response to chemoradiotherapy?. Issue 12 (23rd August 2013) - Molinari, Chiara; Casadio, Valentina; Foca, Flavia; Zingaretti, Chiara; Giannini, Massimo; Avanzolini, Andrea; Lucci, Enrico; Saragoni, Luca; Passardi, Alessandro; Amadori, Dino; Calistri, Daniele; Zoli, Wainer
Abstract Although numerous studies have focused on the link between CpG island methylator phenotypes and the development of colorectal cancer, few studies have dealt specifically with methylation profiling in rectal cancer and its role in predicting response to neoadjuvant chemoradiotherapy (NCRT). We characterized methylation profiles in normal and neoplastic tissue samples from patients with rectal cancer and assessed the role of this molecular profile in predicting chemoradioactivity. We evaluated 74 pretreatment tumor samples and 16 apparently normal tissue biopsies from rectal cancer patients submitted to NCRT. The methylation profile of 24 different tumor suppressor genes was analyzed from FFPE samples by methylation‐specific multiplex ligation‐dependent probe amplification (MS‐MLPA). Methylation status was studied in relation to tissue type and clinical pathological parameters, in particular, pathological response evaluated by tumor regression grade (TRG). ESR1, CDH13, RARB, IGSF4, and APC genes showed high methylation levels in tumor samples (range 18.92–49.77) with respect to normal tissue. Methylation levels of the remaining genes were low and similar in both normal (range 1.91–14.56) and tumor tissue (range 1.84–11). Analysis of the association between methylation and response to therapy in tumor samples showed that only TIMP3 methylation status differed significantly within the four TRG classes (ANOVA, P < 0.05). Results from the present explorative study suggest that quantitative epigenetic classification of rectal cancer by MS‐MLPA clearly distinguishes tumor tissue from apparently normal mucosa. Conversely, with the exception of TIMP3 gene, the methylation of selected genes does not seem to correlate with response to NCRT. J. Cell. Physiol. 228: 2343–2349, 2013. © 2013 Wiley Periodicals, Inc.